Pengaruh Penggunaan Media Dan Metode Bercerita Terhadap Kemampuan Berbahasa Anak Usia 5-6 Tahun Di Kecamatan Reteh Kabupaten Indragiri Hilir Riau - Wanda Husada, Putri; Darmansyah, Rafik (Jurnal Ilmu Multidisiplin, 2023)
This study aims to determine the effect of the storytelling method on language skills in children aged 5-6 years in Kindergarten, Reteh District, Indra Giri Hilir Regency, Riau. This research method is a causal survey in which Umar suggests that this method is a method used to analyze the relationship of variables with other variables. The data analysis technique uses statistics using the t-test with the SPPS 16.0 program. hypothesis testing is carried out using a significance of ???? < 0.050. thus Ho is rejected and Ha is accepted because 0.000 < 0.05. This proves that the storytelling method has an effect on children's language skills.